Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
[tex]x = \frac{-b +/- \sqrt{b^2 - 4ac}}{2a} [/tex]
[tex]x = \frac{-(-8) +/- \sqrt{(-8)^2 - 4(3)(2)}}{2(3)} [/tex]
[tex] x = \frac{8 +/- \sqrt{64 - 24}}{6} [/tex]
[tex]x = \frac{8 +/- \sqrt{40}}{6} [/tex]
[tex]x = \frac{8 +/- 6.31}{6} [/tex]
[tex]x = \frac{14.32}{6} [/tex] x ≈ 2.39
[tex]x = \frac{1.68}{6} [/tex] x ≈ 0.28
[tex]3x^2 - 8x + 2 = 0\\ \\a=3 , \ \ b=-8 , \ \ c=2 \\ \\x_{1}=\frac{-b-\sqrt{b^2-4ac}}{2a} =\frac{8-\sqrt{ (-8)^2-4 \cdot 3\cdot 2}}{2 \cdot 3} =\frac{8-\sqrt{ 64-24 }}{6} =\\ \\ =\frac{8-\sqrt{40 }}{6} = \frac{ 8-\sqrt{4\cdot 10 } }{6} = \frac{ 8-2\sqrt{ 10 }}{6} = \frac{2 (4-\sqrt{ 10 })}{6} = \frac{ 4-\sqrt{ 10 } }{3}[/tex]
[tex]x_{2}=\frac{-b+\sqrt{b^2-4ac}}{2a} =\frac{8+\sqrt{ (-8)^2-4 \cdot 3\cdot 2}}{2 \cdot 3} = \frac{ 4+\sqrt{ 10 } }{3}[/tex]
[tex]x_{2}=\frac{-b+\sqrt{b^2-4ac}}{2a} =\frac{8+\sqrt{ (-8)^2-4 \cdot 3\cdot 2}}{2 \cdot 3} = \frac{ 4+\sqrt{ 10 } }{3}[/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.